The Mueller report illustrated : the obstruction investigation - Mueller, Robert S., III, 1944-; Helderman, Rosalind S. (Scribner, 2019)
"Written and designed by The Washington Post and illustrated by artist Jan Feindt, "The Mueller Report Illustrated: The Obstruction Investigation" brings to life the findings of special counsel Robert S. Mueller III in an engaging and illuminating presentation. When it was released on April 18, Mueller's report laid out two major conclusions: that Russia's interference in the 2016 presidential election had been "sweeping and systematic," and that the evidence did not establish that Trump or his campaign had conspired with the Kremlin. The special counsel left one significant question unanswered: whether the president broke the law by trying to block the probe. However, Mueller unspooled a dramatic narrative of an angry and anxious president trying to control the criminal investigation, even after he knew he was under scrutiny. Deep inside the 448-page report is a fly-on-the-wall account of the inner workings of the White House, remarkable in detail and drama. With dialogue taken directly from the report, The Mueller Report Illustrated is a vivd, factually rigorous narrative of a crucial period in Trump's presidency that remains relevant to the turbulent events of today."--Page [4] of cover.